PENGARUH SKEPTISME PROFESIONAL, INDEPENDENSI, KOMPETENSI, DAN PENGENDALIAN INTERNAL TERHADAP PENDETEKSIAN KECURANGAN (Study Empiris pada Inspektorat Kota Bukittinggi, Payakumbuh, Kabupaten Agam) - Dwiki Kurniawan; M Rasuli; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study is aims to analyze and provide empirical evidence of the (1) The influence of Professional Skepticism against Detection Fraud, (2) The influence of Independece against Detection Fraud, (3) The influence of Competence against Detection Fraud, (4) The influence of internal control against Detection Fraud. The research of this population is auditors working on Inspektorat Kota Bukittinggi, Payakumbuh, dan Kabupaten Agam. This research is populatif, which mean it doesn’t any sampling. Respondents in this research are 66. This research use questionnaire in gathering the data. Data analysis is used by multiple linear regression. The results of this study proves Professional Skepticism has an effect on Detection Fraud. Independece has an effect on Detection Fraud. Competence has no effect on Detection Fraud. Internal Control compensation has no effect on Detection Fraud.Keywords : Professional Skepticism, Independence, Competence, Internal Control, Detection Fraud.